2014
DOI: 10.1208/s12249-014-0212-x
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Generation of Nanometric Structure from Ocimum basilicum Mucilage Prepared for Pharmaceutical Applications

Abstract: Abstract. Plant-derived polymers are widely used in the pharmaceutical industry due to their emollient, lack of toxicity, and irritating nature and low cost. In this work, basil seed mucilage was dried using supercritical carbon dioxide phase inversion technique to form a nanometric structure. The obtained polymeric structures were characterized by scanning electron microscopy (SEM), Brunauer-EmmettTeller (BET) method, and Fourier transform infrared spectroscopy (FTIR) and compared with the ovenderived sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The procedure of mucilage extraction from basil seeds was described in details in our previous work [15]. As stated in the mentioned study, the basil seeds were completely swelled in distilled water.…”
Section: Mucilage Extraction Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of mucilage extraction from basil seeds was described in details in our previous work [15]. As stated in the mentioned study, the basil seeds were completely swelled in distilled water.…”
Section: Mucilage Extraction Proceduresmentioning
confidence: 99%
“…DOI: https://dx.doi.org/10.17352/ijpsdr.000014 nonporous structure for pharmaceutical applications [14]. In the mentioned work, drying procedure was performed using a modifi ed method based on Temtem et al [15] study in which methanol was used as co-solvent to improve water solubility in SC-CO2. In the other previous work, ocimum basilicum mucilage was employed as a cost effective polymeric medium for precipitation of paclitaxel for controlled drug delivery [14].…”
Section: Introductionmentioning
confidence: 99%
“…Khazaei et al [18] characterized the new biodegradable edible film made from OBL seed gum and revealed that it had a good potential to be used in producing edible films for various food applications. Akbari et al [19] used supercritical carbon dioxide phase inversion technique to dry the seed mucilage to form a nanometric structure and they found the bioadhesive property of seed mucilage was good and many active pharmaceutical compounds might be loaded to the resultant nanometric structure to enhance drug release. Naji-Tabasi et al [20] evaluated the potential of OBL seed gum nanoparticles as an oral delivery system for glutathione, which was fabricated by ion gelling technique and calcium was used as a crosslinking agent.…”
Section: Introductionmentioning
confidence: 99%